2021
DOI: 10.3390/jcm10184130
|View full text |Cite
|
Sign up to set email alerts
|

Can Lateralization of Reverse Shoulder Arthroplasty Improve Active External Rotation in Patients with Preoperative Fatty Infiltration of the Infraspinatus and Teres Minor?

Abstract: (1) Background: Postoperative recovery of external rotation after reverse shoulder arthroplasty (RSA) has been reported despite nonfunctional external rotator muscles. Thus, this study aimed to clinically determine the ideal prosthetic design allowing external rotation recovery in such a cohort. (2) Methods: A monocentric comparative study was retrospectively performed on patients who had primary RSA between June 2013 and February 2018 with a significant preoperative fatty infiltration of the infraspinatus and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…An issue that was not explicitly described in these papers was that of the residual rotator cuff function, particularly of the infraspinatus and teres minor muscles. While it has been previously suggested that the lack of a residual rotator cuff can negatively affect the outcomes of RTSA [36,37], more recent studies have suggested a diminishing benefit of a residual rotator cuff for shoulder ROM and function [38,39]. In addition, several studies have also described other factors that may influence the functional outcome scores and ROM post-operatively, such as humeral-head inclination angle, glenosphere size, and lateralisation of the stem [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…An issue that was not explicitly described in these papers was that of the residual rotator cuff function, particularly of the infraspinatus and teres minor muscles. While it has been previously suggested that the lack of a residual rotator cuff can negatively affect the outcomes of RTSA [36,37], more recent studies have suggested a diminishing benefit of a residual rotator cuff for shoulder ROM and function [38,39]. In addition, several studies have also described other factors that may influence the functional outcome scores and ROM post-operatively, such as humeral-head inclination angle, glenosphere size, and lateralisation of the stem [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…Data regarding glenoid and humeral lateralization were combined into one group. For this reason, additional studies comparing the outcomes of humeral and glenoid lateralization are required, as recently proposed by Nabergoj et al [61]. However, these functions differ in regard to force needed to generate overhead ROM as well restoration of ER, which is one of the main findings of the authors results.…”
Section: Discussionmentioning
confidence: 72%
“…One of the advantages of increased humeral offset is the ability to re-tension the remaining rotator cuff and improve deltoid wrap without changing the implant COR [ 20 ]. Deltoid wrap can improve RTSA function due to added compressive stability, as well as improving the mechanical advantage of the posterior deltoid to aid in external rotation [ 20 , 33 ]. Lateralization of the humeral component increases the deltoid wrap effect.…”
Section: Effect Of Implant Design On Functionmentioning
confidence: 99%